Introduction to Design Equity - Miller, Kristine (Open textbook library., 2018)
Why do affluent, liberal, and design-rich cities like Minneapolis have some of the biggest racial disparities in the country? How can designers help to create more equitable communities? Introduction to Design Equity, an open access book for students and professionals, maps design processes and products against equity research to highlight the pitfalls and potentials of design as a tool for building social justice.